Critical Realist Investigation of Real-Time Decision-Making Process Under Uncertainty (Journal of Organizational Psychology, 2021)
The construction of training programs for psychotherapists, requires the production of a practical knowledge database, through research with a coherent epistemology, methodology and method. In order to locate an epistemology which correlated with the researcher-practitioner’s practical approach to knowledge, exploration of existing epistemologies was necessary. The Critical Realist (CR) position enabled composition of the practice approach in coherent academic text. A method for tacit practical knowledge extraction based on dialog between an experienced psychotherapist and his trainee, while she underwent practical training, was developed. Practical knowledge was transferred from teacher to trainee and was transformed while it was apperceived and utilised by the trainee in her practice. A duoethnography was used to contextualise the dialog. That method was elaborated into a collaborative, cyclic research method, which is based on the notion that theories are fallible hypotheses which should be either verified or refuted, in the face of a reality test. In this paper the method is explored and presented including discussion regarding the different roles of the collaborative team members.
Keywords: organizational psychology; psychotherapy, dialogue, tacit practical knowledge, extraction of tacit knowledge, knowledge database, training programs, epistemology, Critical Realism (CR), collaboration, duoethnography, philosopher, practitioner, critique, quality control, fringe division, method, fallible hypothesis, reality test, modes of inference, induction, anomaly detection